Evaluation of Talud Technical Planning on River Regency of Aceh Singkil - Tanjung, Darlina; Sarifah, Jupriah; Pasaribu, Bangun; Lubis, Marwan; Lukman, Anisah; Hasibuan, Abdurrozzaq (International Journal of Engineering and Technology, 2018)
Dynamics that occur in the city of Singkil impact on the development of the city both on socioeconomic aspects as well as in the physical manifestation of talud facilities, which can spur an increase in productivity of a region and the functioning of infrastructure of a city well and smooth. Effect of retaining wall against cliff reinforcement that can protect embankment or beach. By knowing the magnitude of the effect of the safety factor due to the slip, bolster, and the decrease due to the consolidation of the clay layer and the load of the embankment as well as the amount of time of the decline. The crumbling factor (FS guling = 14.97) is greater than the safety factor, for the stability of the slip where the maximum force, where the only force of thrust causing the active horizontal force component (Pa = 0.333) results in a FS (slip) greater than the safety factor of stability to the carrying capacity, the eccentricity value (e = - 0.081) more than 1/6 then the qmin value becomes positive, since the value of e <1/6, and the FS yield of soil bearing capacity (FS (carrying capacity) = 162.122) this value is greater than FS security means the talud safely holds load carrying capacity, safe against bolsters and slip. Â